A Study on Awareness and Adoption of Large Cardamom Production Technology Among Tribal Farmers of North Sikkim - Gudade, B.A.; Deka, T. N.; Chhetri, P.; Bhattarai, N.K.; Vijayan, A.K.; Gupta, U. (Indian Journal of Extension Education, 2012)
Large cardamom (Amomum subulatum Roxb.) is one of the main cash crop grown in Sikkim. It is the lifeline of the people  since it constitutes major share of the economy of the state. A large chunk of agrarian community depends on its  cultivation. The present study was conducted during 2011-12 at Dzongu areas of North Sikkim. A list of the large  cardamom growing villages was prepared and 5 villages were selected randomly. Avillage wise list of the large cardamom  tribal farmers of the selected 5 village was prepared and 25 farmers from each village were randomly selected. Thus, the  total sample consisted of 125 tribal farmers spread over five selected villages. For the purpose of present study, eleven  recommended production technology package of practices about large cardamom production technology viz., improved  varieties, planting material, sucker treatment, field preparation, planting time, method of planting, recommended dose of  manuring, irrigation management, method of weed control, plant protection(bioagents) and improved curing system  were selected. Majority of the respondents were found in medium awareness and high adoption category in practices like  method of field preparation and planting method.
Keywords: Adoption; awareness; large cardamom technology; tribal farmers